Endonura Cassagnau in Iran, with a key to species of the genus (Collembola, Neanuridae, Neanurinae) - Smolis, Adrian (Zookeys, 2016)
Abstract. Three new species of Endonura are described from Iran. Endonura dichaeta sp. n. can be recognized by an ogival labrum, head without chaetae O and E, chaeta D connected with tubercle Cl, tubercle Dl with five chaetae on head, absence of tubercles Di on thorax I and tubercle (Di+Di) of thorax V with 2+2 chaetae. Endonura ceratolabralis sp. n. is characterized by large body size, reduction of labral chaetotaxy, ogival labrum, head without chaeta O and fusion of tubercles Di and De on first thoracic segment. Endonura persica sp. n. is distinguished from its congeners by a nonogival labrum, absence of chaeta O, tubercles Dl and (L+So) with five and eight chaetae respectively and claw with inner tooth. The key to all species of the genus is given.